PENGENDALIAN DIRI, KOMITMEN ORGANISASIONAL DAN PERILAKU CYBERLOAFING TERHADAP KINERJA KARYAWAN (Studi pada Jasa e-Logistik Bisnis di Bandung) - Isniar Budiarti; Luky Pratama (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2022)
The purpose of this study was to determine the effect of self-control variables, organizational commitment, cyberloafing behavior on employee performance. The method used is qualitative and quantitative using a simple random sample, and the selected population is an employee of one of the e-Logistics Business Services in Bandung. The sample of 72 employees was obtained through observation, interviews and distributing questionnaires that have gone through the process of testing and testing the validity, reliability of the instrument. The data from filling out the questionnaire was then analyzed using multiple linear regression analysis techniques with the help of the IBM SPSS 2 Software program. The results of this study indicate that locus of control has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance. Cyberloafing behavior has a positive and significant effect on employee performance, which in this case is the performance of employees of e-Logistics Business Services in Bandung, so it can be stated that the hypothesis in this study is proven.